High-Performance Flexible Tandem Polymer Solar Cell Employing a Novel Cross-Linked Conductive Fullerene as an Electron Transport Layer - Chang, Chih-Yu; Huang, Wen-Kuan; Chang, Yu-Chia; Lee, Kuan-Ting; Siao, Hao-Yi (Chemistry of materials, 2015)
A novel thermally cross-linkable, n-doped conductive fullerene material is developed by incorporating tetrabutylammonium iodide (TBAI) as the dopant into an azidofullerene derivative PCBN3. The application of TBAI-doped cross-linked PCBN3 film as the electron transport layer (ETL) in polymer solar cells (PSCs) delivers several remarkable features, including easy solution-processability, reasonable electrical conductivity (2.8 × 10–3 S cm–1), good ambient and chemical stability, fine-tunability of the work function of the electrode, wide applicability in a variety of efficient polymers, relative weak thickness-dependent performance property, and moderate cross-linking temperature (∼140 °C). With this ETL, a single-junction solar cell based on the blend of poly[[4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl][3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl]] (PTB7) with [6,6]-phenyl-C71-butyric acid methyl ester (PC71BM) delivers a power conversion efficiency (PCE) up to 8.8%, which is superior to that of the device with state-of-the-art ETL titanium oxide (TiO x ) film. In addition, the application of using this ETL in double-junction tandem structure solar cells is also demonstrated, with a PCE exceeding 10%. More significantly, the low processing temperature of this ETL makes it compatible with the fabrication of flexible tandem solar cells, and an impressively high PCE of 9.2% is demonstrated, which represents the highest PCE ever reported for flexible PSCs.